Pola Interaksi Sosial Anak Autis di Sekolah Penyelenggara Pendidikan Inklusif di Kota Padang - Ade Fransiskus Tarigan; Marlina Marlina (Pusat Pengembangan Ilmiah dan Penelitian Mahasiswa Universitas Negeri Padang, 2019)
This research revealed about the social interaction patterns of children with autism in the education inclusive school of SMKN 7 Padang which described the patterns of social interaction of children with autism in SMKN 7 Padang with students with special needs, normal students, subject teachers and accompanying teachers special. The basis of this research is that researchers found that children with autism were always accompanied and waited by their mothers wherever the child left, even his mother accompanied the child during the learning process that took place in the classroom. This study uses a research method with a qualitative descriptive approach. The subjects in this study were children with autism. Respondents in this study were students and teachers at SMKN 7 Padang. The results of this study are a description of the way an Aulia gives a response to a greeting from her friend in a loud voice, answers the teacher's question without raising his hand up, leaves the counseling room without permission and runs immediately, responding to his friend's invitation saying yes and go together, sometimes he also refused and did not give a response to his friend and then played his cellphone.